A critical discourse analysis of online game advertisements in english - Phạm,Thị Hồng Hạnh (2016)
This study presents an attempt to apply a Critical Discourse Analysis perspective to investigate 50 online game advertisements in English. The data for analysis in this thesis is taken from official websites of companies publishing online game products in the United States. The study is based on the theory of Critical Discourse Analysis introduced by Norman Fairclough, following a framework with three parts: Description, Interpretation and Explanation. It focuses on the analysis of linguistic features (lexical and grammatical features and textual structure), the discourse process and social process. The findings show that the advertisers employ linguistic features and persuasive strategies to represent their power and ideology which implicitly influence and manipulate their customer's perception and behavior. Hopefully, the results of the study will provide some practical applications for teaching and learning English. This study may be useful for those who are interested in investigating advertising discourse, especially through the lens of CDA.